Luminous environmental comfort in classrooms in Northeast Brazil - Almeida, Gylnara Kylma Feitosa Carvalhêdo; Almeida, Will Ribamar Mendes; Ferreira, Miguel Jânio Costa; Carvalho, Gabriela Ferreira; Pinto, Guilherme Gonçalves Silva; Nascimento, Ana Lourdes Avelar; Gonçalves, Maria Claudia (Ciência e Natura, 2018)
The objective of this article was to evaluate the light conditions in classrooms at a school in the northeast of Brazil and their influence on learning. The illuminance of the rooms was evaluated during solstices and equinoxes. We used NBR 15215-04 and measured light a 16 points using a digital lux meter. Also, perceptions of luminous comfort were ascertained through a questionnaire administered to teachers and students. Only 18% of the evaluated points were within the range of luminosity considered adequate according to the NBR, and the perceptions of teachers and students coincided with the technical results, as the light levels were considered unsatisfactory. According to the teachers, poor lighting affects school activities and the behavior of students, and we recorded complaints of visual discomfort and headaches. The lighting in the evaluated rooms was not adequate in terms of the comfort and quality of student learning. Low-cost strategies aimed at improving visual comfort—and, consequently, student learning—are suggested.